Gaya Komunikasi Prabowo-Gibran dalam Debat Calon Presiden Indonesia 2024 - Sulton, Fullisal Achmad; Aflah, Muhammad Ferdinand; Suryadilaga, Sulthon Akbar (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This study aims to analyze the communication styles of presidential candidate pair Prabowo Subianto and Gibran Rakabuming Raka in the 2024 presidential election debates broadcast on television. The method used is quantitative content analysis of debate recordings, focusing on verbal and non-verbal language, ways of conveying messages, and responding to debate opponents. The results show significant differences in the communication styles of the two candidates. Prabowo Subianto tends to use an aggressive communication style that reflects his character as a firm and confrontational leader, while Gibran Rakabuming Raka more often displays a passive communication style that indicates a more accommodative approach and avoids conflict. These findings provide insight into how communication styles can reflect candidate personalities, backgrounds, and political strategies in an effort to gain voter support. The implication is that candidates, campaign teams, political parties, and the media need to strategically design and align communication styles with voter preferences and other campaign elements. However, further research is needed with wider media coverage, a multi-method approach, and linking with other variables to get a more comprehensive picture of the dynamics of communication styles in political contestation in Indonesia.